De Novo CSNK2B Mutations in Five Cases of Poirier–Bienvenu Neurodevelopmental Syndrome - Yang, Qi; Zhang, Qinle; Yi, Shang; Qin, Zailong; Shen, Fei; Ou, Shang; Luo, Jingsi; He, Sheng (Frontiers in Neurology, 2022)
Abstract Poirier–Bienvenu neurodevelopmental syndrome is an autosomal dominant disorder characterized by intellectual disability and epilepsy. The disease is caused by mutations in the CSNK2B gene, which encodes the beta subunit of casein kinase II, and it has important roles in neuron development and synaptic transmission. In this study, five Chinese patients were diagnosed with Poirier–Bienvenu neurodevelopmental syndrome caused by CSNK2B mutations by whole exome sequencing. We detected four de novo variants of the CSNK2B gene in these five unrelated Chinese patients: two novel mutations, namely, c.100delT (p.Phe34fs*16) and c.158_159insA(p.Asp55fs*4), and two recurrent mutations, namely, c.1A>G (p.Met1?) and c.332 G >C (p.R111P). All five patients showed mild-to-profound intellectual disabilities/or learning disabilities and developmental delays, with or without seizures. Although intellectual disability/developmental delay and epilepsy are the most common manifestations of CSNK2B deficiency, the clinical phenotypes of probands are highly variable, and there is no significant correlation between genotype and phenotype. An abnormal stature may be another common manifestation of CSNK2B deficiency. Here, we report the effects of growth hormone (GH) therapy on the patients’ linear height. In conclusion, Poirier–Bienvenu neurodevelopmental syndrome is a highly heterogeneous disease caused by mutations in the CSNK2B gene. The phenotype was highly variable, and no significant correlation of genotype and phenotype was found. Short-stature patients with CSNK2B deficiency may benefit from GH therapy. The identification and characterization of these novel variants will expand the the genotypic and phenotypic spectrum of Poirier–Bienvenu neurodevelopmental syndrome.